Challenges and Responses for Ensuring Sustainability of INSA Training Programs - Jongsook Kim; Hyung-kyung Lee; Jin-young Lee (International Journal of Nuclear Security, 2016)
Providing a systematic training is critical for a state or international perspective to reinforce nuclear security regime nationally or internationally. Korea government recognizes the importance of such challenge, and established the INSA under the KINAC as a Center of Excellence for fostering national nuclear security capacity and contributing international nuclear security governance. INSA started with the government policy that the establishment of sustainable education and training infrastructure and processes is fundamental to the capacity building strategy. After established, INSA has been designing and delivering the domestic and international/regional training programs for the purpose of fostering human resources development in nuclear nonproliferation and security since Feb. 2014. This paper will cover a couple of new exercise modules which will be introduced newly in INSA training courses to achieve and ensure objectives of provided training programs.
Keywords: nuclear secuirty; training; exercise module; SETT